2021
DOI: 10.3389/fcvm.2021.736042
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Risk of Procedural Complications in Patients With Atrial Fibrillation Undergoing Catheter Ablation

Abstract: Background: Little is known about the prognostic value of nutritional status among patients undergoing atrial fibrillation (AF) catheter ablation (AFCA). We compared the risk of procedure-related complications and long-term rhythm outcomes of AFCA according to nutritional status.Methods: We included 3,239 patients undergoing de novo AFCA in 2009-2020. Nutritional status was assessed using the controlling nutritional status (CONUT) score. The association between malnutrition and the risk of AFCA complications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In the Vijan et al study, independent factors affecting LOHS (≥7 days for this study) included ACS, decompensated HF, increased NT-proBNP levels and infections ( 25 ). Researchers studying nutritional status confirm that malnutrition upon hospital admission is quite common and is associated not only with prolonged hospital stay but also with worse prognosis ( 28 31 ). Malnutrition also increases the risk of re-hospitalization in patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…In the Vijan et al study, independent factors affecting LOHS (≥7 days for this study) included ACS, decompensated HF, increased NT-proBNP levels and infections ( 25 ). Researchers studying nutritional status confirm that malnutrition upon hospital admission is quite common and is associated not only with prolonged hospital stay but also with worse prognosis ( 28 31 ). Malnutrition also increases the risk of re-hospitalization in patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al showed that it increases the risk of complications in AF patients undergoing catheter ablation. The overall complication rate was more marked among malnourished women (7.1%) than malnourished men (3.7%) (28). Monitoring patients' nutritional status is essential to the medical care process, as it can deteriorate during a hospital stay (29).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the recurrent AF burden or the operators’ discretion, gap fillings for the reconnected PVs or an empirical extra-PV ablation, such as a posterior wall isolation, have been performed ( Lee et al, 2019 ). In patients with a well-maintained PVI during redo-mapping, extra-PV triggers play a significant role in AF recurrence, and the outcomes of a repeat ablation are worse than in patients with PV reconnections ( Kim et al, 2021 ). In this study, we examined the AF maintenance mechanism during the PVI-gap state by using computational models made with the electroanatomical maps of 40 patients, most of whom had persistent AF.…”
Section: Discussionmentioning
confidence: 99%